Prevalence of Dental Caries in Children (Update Dental College Journal, 2021)
This cross sectional study on oral condition among school going children in Sylhet city was conducted at Osmani Medical High School, Dorgah Gate, Sylhet, Bangladesh. This study was carried out on 8th October, 2019 among 208 students, mostly 12 years aged studying in Class VI. The main objective of the study was to assess the oral health condition of school going children through decayed, missing, and filled teeth (DMFT) status. Data was collected by personal interview and clinical examination of the respondents. Among 208 children, 96 (46.2%) were boys and 112 (53.8%) were girls. Among all, 63 (30.3%) respondents brush their teeth once daily while 137 (65.9 %) respondents brush twice a day, and 8 (3.8 %) of them brush their teeth more than twice daily. Fluoride containing toothpaste is used by 73 (35.1 %) students, 112 (53.8 %) students did not know whether their toothpaste contain fluoride or not, and 23 (11.1 %) students do not use fluoride. Among all respondents, 125(60.09 %) did not have any decayed tooth, while 83(39.90 %) had tooth decay, and 20(9.6 %) had their teeth filled. Normal gingival condition was found in 185 (88.94 %) subjects, but 23(11.06 %) of them had red or swollen gingiva. The mean DMFT of the study population was 1.19 which is considered as “low” according to “WHO quantification for the DMFT index”.Update Dent. Coll. j: 2021; 11 (1): 4-6